Climate Justice and Sustained Transnational Mobilization - Paul Almeida (Journal of World-Systems Research, 2019)
Samir Amin’s final essay called for the creation of a new international organization of progressive social forces. This essay provides evidence from twenty-first century transnational movements on the likelihood of the emergence of such an international organization and the issues and sectors most likely to facilitate coalitional unity.  More specifically, the ecological crises identified by Amin in the form of global warming and climate change create an unprecedented global environmental threat capable of unifying diverse social strata across the planet.  The climate justice movement has already established a global infrastructure and template to coordinate a new international organization to confront neoliberal forms of globalization.  Pre-existing movement organizing around environmental racism, climate justice in the global South, and recent intersectional mobilizations serve as promising models essential to building an enduring international organization representing subaltern groups.